Isolation of an anti-HIV compound from Elaeodendron croceum (Thunb.) DC. - Meyer, J.J.M. (Jacobus Johannes Marion) (University of Pretoria, 2013)
Thesis (PhD (Plant Physiology))--University of Pretoria, 2007.